Expectations, shocks, and asset returns - Sousa, Ricardo M. (2007)
I use the consumer’s budget constraint to derive a relationship between stock market returns, the residuals of the trend relationship among consumption, aggregate wealth, and labour income, cay, and three major sources of risk: future changes in the housing consumption share, cr, future labour income growth, lr, and future consumption growth, lrc. Using a VAR, I compute measures of expected and unexpected long-run changes of the major determinants of asset returns and find that: (i) cay, cday, expected lr, cr, lrc and expected long-run changes in ex-ante real returns, lrret, strongly forecast future asset returns; (ii) unexpected lrc and unexpected lrret contain some predictive power for asset returns; (iii) unexpected lr and unexpected cr do not predict future asset returns. One can, therefore, use the intertemporal budget constraint and the forecasting properties of an informative VAR to generate the predictability of many economically motivated variables developed in the literature on asset pricing. The framework presented is sufficiently flexible to accommodate the implications of a wide class of optimal models of consumer behaviour without imposing a functional form on preferences.